I-CLORE Teaching Material Based on Katupat Kandangan Local Wisdom on the Topic of Heat and Temperature - Lutfiyanti Fitriah (Berkala Ilmiah Pendidikan Fisika, 2021)
The research aimed to focus on describing the practicality of teaching material based on katupat Kandangan local wisdom which arranged by I-CLORE (Islamic-Connecting to Local Wisdom, Organizing, Reflecting, dan Extending) learning model. This research was a research and development study, with the development model of ADDIE. The subjects of this research were first-semester students of the 2019/2020 academic year in the Physics Education Department, Faculty of Education and Teacher Training of UIN Antasari Banjarmasin who learned Fundamental of Physics 1. The data were obtained through the questionnaire and observation sheet. The data were analyzed quantitatively and qualitatively. The result of the research showed that the practicality was very good because the mean score of easy to use, benefit, time efficiency, and interest was 4.29. Then, the mean score of lecturer activities implementation and the mean score of student activities implementation were 4.72 and 4.31 in very good category. The conclusion of this research is the teaching material was practical. Therefore, this teaching material can be used in Fundamental of Physics 1 course and tested in another experiment with a larger sample.